Faktor-Faktor Penyebab Kejadian Preeklamsia/Eklamsia Pada Ibu Bersalin di Ruang Bersalin Rumah Sakit Umum Daerah Panembahan Senopati Bantul - Mahayanti, Agnes; Ngatini (STIKes Panti Rapih, 2021)
Background: Preeclampsia / eclampsia is the second leading cause of maternal death in Indonesia, which be marked by an increase in blood pressure, positive urine protein and edema. Objective: The purposes of this study to determine the factors that cause the incidence of preeclampsia / eclampsia in delivery women in Labour Room Of Panembahan Senopati Hospital Bantul. Methods: This study used a cross sectional design. The research subjects were 86 mothers giving birth from January-June 2019. The data analysis technique used univariate analysis with frequency distribution, bivariate analysis with chi-square and multivariate analysis was used to determine the Fiiting Information Model, Pseudo R-Square and parameter estimates of causal factors. the occurrence of preeclampsia / eclampsia. Results: 58.1% of respondents had preeclampsia / mild eclampsia, 41.9% were moderate preeclampsia / eclampsia. The results of the C-square analysis p value <0.05 was found in the variables of chronic disease, maternal age, family planning, ANC and maternal education. The Chi-Square statistical value is 2466.177 (Pearson) (> 90.00) with a significance value of 0.000 (<0.000). The independent variables of chronic disease, maternal age, family planning, ANC and maternal education contributed 62.2% to the incidence of preeclampsia / eclampsia. Conclusion: Factors causing the incidence of preeclampsia / eclampsia in women giving birth at Panembahan Senopati Hospital include chronic disease with a p-value of 0,000, maternal age with a p value of 0,000, ANC examination behavior with p value of 0.00, family planning with p value of 0.013 , maternal education with a p value of 0.013. Variables history of complications, parity did not have a significant effect on the incidence of preeclampsia/eclampsia in women who gave birth. From the results of this study, it is hoped that it can provide useful knowledge about factors that are closely related to the incidence of preeclampsia and eclampsia so that pregnant women with one or more factors can get attention for health workers so that prevention can be carried out.